Regulation of endothelial nitric oxide synthase by tetrahydrobiopterin in vascular disease. - Alp, N; Channon, K (2004)
Nitric oxide (NO), produced by endothelial nitric oxide synthase (eNOS), is a key signaling molecule in vascular homeostasis. Loss of NO bioavailability due to reduced synthesis and increased scavenging by reactive oxygen species is a cardinal feature of endothelial dysfunction in vascular disease states. The pteridine cofactor tetrahydrobiopterin (BH4) has emerged as a critical determinant of eNOS activity: when BH4 availability is limiting, eNOS no longer produces NO but instead generates superoxide. In vascular disease states, there is oxidative degradation of BH4 by reactive oxygen species. However, augmentation of BH4 concentrations in vascular disease by pharmacological supplementation, by enhancement of its rate of de novo biosynthesis or by measures to reduce its oxidation, has been shown in experimental studies to enhance NO bioavailability. Thus, BH4 represents a potential therapeutic target in the regulation of eNOS function in vascular disease.